ANALISIS TATA KELOLA PENANGANAN ANAK TIDAK SEKOLAH (PATS) BERBASIS PRINSIP GOOD GOVERNANCE OLEH PEMERINTAH DAERAH MELALUI OPD DI KABUPATEN JEPARA - Rosse F. M. Nainggolan; Rina Martini (Journal of Politic and Government Studies, 2026)
The issue of Out-of-School Children (OSC) remains a serious challenge in human resource development in Indonesia, including in Jepara Regency. Despite the implementation of various educational policies and programs, there are still school-age children at the local level who do not have access to formal or non-formal education. This condition indicates that the problem of OSC is not solely related to educational access but is also influenced by social and economic factors, as well as the quality of local governance in coordinating and implementing handling policies. Therefore, the management of OSC should be examined not only from an educational perspective but also from the standpoint of local governance. This study aims to analyze the governance of Out-of-School Children management implemented by the Jepara Regency Government through Regional Apparatus Organizations (OPD) based on the principles of good governance. The research employs a qualitative approach with a descriptive research design. Data were collected through in-depth interviews with relevant OPDs, including the Regional Development Planning Agency (Bappeda) as the leading sector, the Department of Education, Youth and Sports, the Department of Social Affairs, Community and Village Empowerment, the Office of Women’s Empowerment and Child Protection and Family Planning (DP3AP2KB), Community Learning Centers (PKBM), and beneficiaries of the OSC handling program. Data collection was also supported by documentation and literature review to strengthen the validity of the findings. The analysis was conducted using the principles of good governance developed by the United Nations Development Programme, which include participation, rule of law, transparency, responsiveness, equity, effectiveness and efficiency, and accountability. This framework was applied to assess the extent to which the governance of OSC management in Jepara Regency has been implemented in accordance with good governance principles, as well as to identify supporting and inhibiting factors in policy implementation at the local level. The findings reveal that the Jepara Regency Government has implemented OSC governance through cross OPD coordination, data collection and verification, the implementation of the 12-year compulsory education program, the provision of educational assistance, and the utilization of non-formal education pathways through Community Learning Centers (PKBM). The application of governance principles is particularly evident in the aspect of responsiveness, although challenges remain in terms of service equity, program effectiveness, and sustainability. Therefore, strengthening cross-sectoral coordination, policy innovation, and community participation is necessary to optimize sustainable OSC management.